(untitled) (Biological Sciences - PJSIR, 2002)
The laxative effect of cumin seeds was investigated. Seeds from the plant, cuminium cyminium were obtained from India . Their aqueous extract (Aq. extract) was prepared and phytochemical analysis confirmed the presence of saponin s and glycosidic sugars. The extract of cumin, senna suspension and saline solution (as control) were administered to different groups of rats and the cumulative number of wet faeces passed before and after administration were counted for a period of 24 h. Both the extract of cumin and senna suspension increased the number of wet faeces compared to the control. The effect of 4g kg- 1 Aq . extract was comparable to 2g kg-1 senna suspension. The Aq. extract also contracted the guinea pig ileum in a dose dependent manner. The contraction curve was shifted to the right significant by atropine (P < 0.05), but was not significantly affected by dibenzyline, hexamethonium or papaverine. The study has thus demonstrated the laxative effect of cumin seeds. It may be suggested that this effect could be mediated by increase in motility through stimulation of muscurinic receptor s. However , further work has to be done on this to prove the mechan ism of action .